Kant's Alleged Ambiguity Toward Leibniz: Revisiting the Critique of Dogmatism - Gutiérrez-García, José Antonio (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This paper discusses Kant’s critique of Leibniz, especially in the Amphiboly of the Concepts of Reflection in the Critique of Pure Reason. Although Kant’s early criticism suggests an identification of Leibniz with Wolffian dogmatism, later texts reveal a more nuanced attitude, distinguishing between Leibniz’s own metaphysics and its early reception. Examining the four central pairs of concepts of reflection–identity/diversity, agreement/opposition, inner/outer, and matter/form, this article shows that what Kant primarily criticizes is a form of Leibnizianism popularized through Wolff, rather than Leibniz himself. Drawing on Leibniz’s writings, it is shown that the alleged ambiguity in Kant’s position toward Leibniz reflects a certain development in his thought: namely, a movement from critique toward partial retrieval. This study is relevant not only to the question of Leibniz’s reception in the eighteenth century, but also to understanding Kant’s relationship to the rationalist tradition, which he sought both to overcome and to preserve.